Factors influencing nurse turnover intention at private Hospitals in Purwokerto in 2024 - Rahmansyah, Ilham; Aji, Budi; Suratman, Suratman; Arum, Khusnul Khotimah (Institute of Computer Science (IOCS), 2025)
The turnover intention rate among nurses in hospitals in Indonesia is quite high, exceeding 10% annually (above the normal limit). This phenomenon also occurred in Purwokerto, where in 2023 the turnover rate exceeded the minimum threshold of 10% per year. The causes of nurse turnover intention include workload, work stress, perceived organizational support, job satisfaction, and compensation. Nurse turnover intention can lead to a decrease in trained and expert nurses in their field. Method: This study used a cross-sectional design with 302 respondents from 6 private hospitals in Purwokerto. The sampling technique was stratified proportional random sampling. Data were collected using questionnaires, and the analysis employed binary logistic regression with the enter method. Results: The analysis of the relationship between workload, work stress, perceived organizational support, job satisfaction, and compensation on nurse turnover intention showed a p-value <0.001. Multivariate analysis using the enter method found that workload and work stress had significant effects (p = 0.001), while perceived organizational support (p = 0.368), job satisfaction (p = 0.125), and compensation (p = 0.175) did not have significant effects. Conclusion: There is a relationship between workload, work stress, perceived organizational support, job satisfaction, and compensation with nurse turnover intention. However, multivariate analysis shows that workload and work stress simultaneously influence nurse turnover intention in hospitals.